2009
DOI: 10.1016/j.bbamcr.2009.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Insulin induced phosphorylation of prohibitin at tyrosine114 recruits Shp1

Abstract: Prohibitin (PHB or PHB1) is an evolutionarily conserved ubiquitously expressed multifunctional protein and is present in various cellular compartments. Phosphorylation of PHB has been suggested as one of the potential mechanisms in the regulation of its various functions however exact sites of phosphorylation remain to be determined. To better understand the functional relevance of phosphorylation of PHB, we have explored the potential sites of phosphorylation using combination of approaches including phosphoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 27 publications
2
72
0
Order By: Relevance
“…The PHB1⅐PHB2 phosphocomplex is required for mitochondrial homeostasis and survival of human T cells (47). Insulin-induced phosphorylation of cell membrane PHB1 at tyrosine 114 and 259 by insulin receptor kinase facilitates its interaction with Shp1, which in turn negatively regulates PIP3/Akt signaling in myoblasts (48) and breast cancer cells (48,49). On the other hand, Akt-induced threonine 258 phosphorylation of PHB1 inhibits its interactions with PIP3 and Shp2, which may facilitate insulin-induced PIP3/Akt signaling in 3T3-L1 adipocytes (50).…”
Section: Discussionmentioning
confidence: 99%
“…The PHB1⅐PHB2 phosphocomplex is required for mitochondrial homeostasis and survival of human T cells (47). Insulin-induced phosphorylation of cell membrane PHB1 at tyrosine 114 and 259 by insulin receptor kinase facilitates its interaction with Shp1, which in turn negatively regulates PIP3/Akt signaling in myoblasts (48) and breast cancer cells (48,49). On the other hand, Akt-induced threonine 258 phosphorylation of PHB1 inhibits its interactions with PIP3 and Shp2, which may facilitate insulin-induced PIP3/Akt signaling in 3T3-L1 adipocytes (50).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of prohibitins modulated their effects on cell signalling and function (Mishra et al 2010). Insulin phosphorylated PHB1 at Tyr114, which is conserved in PHB2, resulting in SHP1 recruitment and decreased AKT phosphorylation (Ande, et al 2009). …”
Section: Prohibitin-2mentioning
confidence: 99%
“…23,31 The following primers were used to generate IRE mutant (mIRE) reporter constructs: À1031/À1025 mutant, forward 5 0 -C GTCTCTACAAAAATAAAAAATTAGCCGGGTGTCCCCCCGCATGCCTGTAATCTCA GCTATTCTG-3 0 reverse 5 0 -CAGAATAGCTGAGATTACAGGCATGCGGGGGGA CACCCGGCTAATTTTTTATTTTTGTAGAGACG-3 0 and À1010/À1004 mutant,…”
Section: Materials and Methods Reagentsmentioning
confidence: 99%
“…24,27,36 Furthermore, we have shown that phosphorylation of PHB at tyrosine114 (Tyr114) residue attenuates PI3K/Akt signaling. 23,24 In this study, we tested whether forced expression of PHB would change insulin-induced adipogenesis. To determine this, we used 3T3-L1 fibroblasts as a model cell line.…”
Section: Phb Modulates Insulin-induced Adipogenesismentioning
confidence: 99%
See 1 more Smart Citation